A REVIEW: THE NATURAL ANTIOXIDANT ACTIVITY OF BLACK MULBERRY AND ITS OTHERS FUNCTION - ANDRIATI KHOERUNNISA; Insan Sunan Kurniawansyah (Farmaka, 2018)
Antioxidants are compounds that can be synthetic or natural products. These compounds have a mechanism which suppresses or delays the oxidation process of other molecules because of free radicals. Free radicals such as reactive oxygen species (ROS) are produced during cellular metabolism and environmental such as heavy metal ions, cigarette smoke. Natural antioxidants have been developed from several parts of the plants which contain flavonoids, phenolic acids, tannins, quinones and other phenolic compounds. One of the many plants examined for its antioxidant activity is black mulberry (Morus nigra L.). Black mulberry is known for their high content of phenolic compound. Thus have high antioxidant activity. This review attempt to focus on the relationship between antioxidant activity of black mulberry and composition of phytochemicals, especially phenolic compounds in black mulberry and to explore other potential functions of black mulberry in medicinal uses.